A Recent Update on Therapeutics to Treat Emerging n-COVID 19: A Review - Ashique, Sumel; Sandhu, Navjot K.; Haque, Sk. N.; Koley, Kartick (Coronaviruses, 2021)
A coronavirus is a group of nonsegmented, single-stranded, enveloped viruses having positive RNA genomes. This virus was first described in 1931, and the first coronavirus was isolated (HCoV-229E) from humans in 1965. People be-come infected with four human coronavirus strains: 229E, NL63, OC43, and HKU1, which cause respiratory associated problems such as SARS and MERS. Lately, a new version of a strain called SARD-CoV-2 has been found. WHO called it novel coronavirus-infected pneumonia (NCIP) and later officially renamed as COVID-19 on 11th Feb 2020. The outbreak began in Wuhan, Hubei, China, in Dec 2019 and from now the outbreak becomes pandemic. Here, we have reviewed various categories of therapeutics, vaccines, and clinically investigated drugs to treat and prevent n-COVID-19. Till now, no specific FDA approved drugs or vaccines are available against n-COVID-19. Several options can be visualized to control or prevent emerging infections, including antivirals, immunomodulators, interferons, vaccines, monoclonal antibodies, and bio- molecules. Given the urgency of the outbreak, we have discussed some potential existing therapeutics for treating n-COVID-19.
Keywords: coronaviruses